2005
DOI: 10.1016/j.cardiores.2005.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctional remodeling by hypoxia in cultured neonatal rat ventricular myocytes

Abstract: Short-term hypoxia (5 h) decreases Cx43 protein and conduction velocity, thereby contributing to the generation of an arrhythmogenic substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
59
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 40 publications
3
59
0
Order By: Relevance
“…37 The exposure to hypoxia also resulted in a 50% reduction of Cx43 protein expression and an approximately 20% decrease in CV of cultured neonatal rat cardiomyocytes. 38 However, some recent investigations have shown that the slowing of impulse propagation depends on more severe reductions in Cx43 abundance. 3,39 The fluidity of cholesterol-rich domains in plasma membrane is important to gap junctional coupling.…”
Section: Discussionmentioning
confidence: 99%
“…37 The exposure to hypoxia also resulted in a 50% reduction of Cx43 protein expression and an approximately 20% decrease in CV of cultured neonatal rat cardiomyocytes. 38 However, some recent investigations have shown that the slowing of impulse propagation depends on more severe reductions in Cx43 abundance. 3,39 The fluidity of cholesterol-rich domains in plasma membrane is important to gap junctional coupling.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cx43 expression decreases 60 min after coronary artery occlusion in the rat. 21 During the course of hypoxia in cultured neonatal rat cardiomyocytes, the total Cx43 level increases after 15 min and then decreases after 5 h. 22 Ischemia enhances dephosphorylation of Cx43 in isolated cardiomyocytes 23 and in the perfused rat heart 17 after 30 and 15 min, respectively.…”
mentioning
confidence: 99%
“…While previous studies assessed connexin modulation only in ventricular myocytes (Beardslee et al 2000;Kostin 2001;Zeevi-Levin et al 2005;Matsuschita et al 2006), this is the first study on connexin remodeling in adult atrial cells, showing that both hypoxia and ischemia are potent modulator of Cx43 redistribution and that the latter can be, in some cases, reversible. In the first part of our study, we observed a significant downregulation of Cx43 expression in atrial cells during hypoxia, confirmed by Western Blot analysis and qualitative immunofluorescence, demonstrating at the same time how the hypoxic insult acts specifically on Cx43, since qualitative immunofluorescence did not confirm the same trend for ZO-1, an essential constituent of intercalated disk required for the proper formation of Cx43 gap junctions (Laing et al 2007;Palatinus et al 2011), and for Cx40 protein levels.…”
Section: Hypoxia/reoxygenation and Connexin Remodeling: Cx43 Modulationmentioning
confidence: 78%
“…The aforementioned data can be partially confirmed by several studies in ventricular myocytes. Zeevi-Levin et al (2005) demonstrated that 5 h of hypoxia decreased Cx43 protein in rat ventricular myocytes, without a concurrent reduction of mRNA levels. In our study, Cx43 mRNA downregulation at 48 h of hypoxia in atrial cells could be explained by specific regulation of connexins in different species (rat versus mouse) and tissues (ventricle versus atrium) (Kostin 2001).…”
Section: Hypoxia/reoxygenation and Connexin Remodeling: Cx43 Modulationmentioning
confidence: 93%